Penyuluhan tentang Pentingnya Peran Bidan dalam Meningkatkan Kesiapan Persalinan pada Ibu Hamil Trimester III di Klinik Hj. Nuracmi, S.ST., Bdn., M.Kes Kota Palembang Tahun 2025 - Merisa Riski; Wahyu Ernawati; Ratna Dewi; Rika Maisaroh; Azka Ryanita (LPPM Akbid Harapan Ibu Pekalongan, 2026)
Maternal and neonatal mortality remain important public health concerns that require continuous promotive and preventive efforts, including improving maternal readiness for childbirth. Midwives play a strategic role as educators and companions in preparing pregnant women for safe and planned delivery. This community service activity aimed to improve the knowledge of third-trimester pregnant women regarding the importance of the midwife’s role in childbirth preparation. The activity was conducted at Hj. Nuracmi Clinic, Palembang City, in January 2025, involving 20 third-trimester pregnant women. A health education intervention was implemented using a one-group pretest–posttest design. Knowledge levels were assessed before and after the counseling session using a structured questionnaire and analyzed descriptively. The results showed that prior to the intervention, 40% of participants had low knowledge levels, whereas after the counseling, all participants (100%) demonstrated good knowledge. These findings indicate that counseling is effective in increasing pregnant women’s understanding of the midwife’s role in childbirth preparation. This community service activity contributes to enhancing maternal readiness for childbirth and supports promotive and preventive efforts to reduce the risk of childbirth complications.